Fenomena Relawan Demokrasi pada Pesta Politik di Kabupaten Pasaman Barat - Royjul Huda; Zulkarnain (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to explore the phenomenon of democracy volunteers in Pasaman Barat Regency. The phenomenon of democracy volunteers in the 2024 elections in Pasaman Barat Regency shows an increase in political participation among the community. However, there are challenges associated with potential clientelism practices and limited volunteer resources that can affect the integrity of elections. The purpose of this research is to analyze the role and impact of democracy volunteers in the 2024 elections in Pasaman Barat, as well as to understand the challenges they face and how they influence the electoral process. This research employs a phenomenological type of study with a qualitative approach, focusing on political volunteers in Pasaman Barat Regency. The results of the democracy volunteers in Pasaman Barat Regency play an important role in expanding the voter base and increasing political participation. They also face challenges such as limited resources and the influence of political money. Volunteers tend to come from the general public with personal interests and often serve as a shortcut for political elites. Although it has a positive impact on participation and transparency, the presence of volunteers also reveals the potential for transactional political practices. The working mechanism of volunteers, including socialization and direct support to the community, demonstrates their efforts in enhancing political literacy and supporting candidates, despite the risks of a shift towards mass leadership.